HUBUNGAN KUALITAS PELAYANAN TENAGA KESEHATAN DENGAN KEPUASAN PASIEN DI RUANG RAWAT INAP RSU MITRA SEJATI KECAMATAN MEDAN JOHOR KOTA MEDAN TAHUN 2020 - Jabbar, Mimi Wahyuni (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
Health development is the implementation of health efforts by the Indonesian people, to increase awareness, willingness and ability to live a healthy life for everyone, so as to realize the highest degree of public health. Data from Mitra Sejati Hospital in Medan City recorded fluctuations in the number of inpatient visits at Mitra Sejati Hospital in Medan City. The purpose of this study was to analyze the effect of the relationship between the quality of public health services and patient satisfaction in Mitra Sejati Hospital in Medan City in 2020. This type of research uses quantitative methods conducted an analytical survey with a cross sectional study approach. Population in this study were all patients who visited Mitra Sejati Medan City Hospital in 2020 with an average number of visits of 220 patients. The sampling technique used Stratified random sampling of 69 patients. Data analysis in this study used univariate analysis, bivariate analysis and multivariate analysis with logistic regression. The results of the study with the chi square test revealed the value of p value variable reliability was 0,000 <0.05, assurance was 0.001 <0.05, tangible was 0,000 <0.05, empathy was 0.001 <0.05 and responsiveness was 0,000 <0.05 . Logistic regression test results revealed that the reliability variable has the largest Exp (B) value = 55.614. The conclusion of this study is that there is a relationship of reliability, assurance, tangible, empathy and responsiveness with patient satisfaction at the Medan Sejati General Hospital in 2020. The most dominant variable related to patient satisfaction is the reliability variable. Suggested to Mitra Sejati Hospital, Medan City to further improve the quality of service and maintain good quality so that patient satisfaction can be achieved optimally.